(untitled) (Bangladesh Journal of Livestock Research, 2020)
This study was conducted by using annual research investment data of BLRI to estimate the impact of livestock research generated technologies on national economy of Bangladesh. The results showed that the livestock research investment was increased and consequently contribution in GDP of livestock sector was also increased. The result of Chow Test F1,35= 4.35 indicated that there is a great positive impact of livestock technologies on livestock Gross Domestic Product (GDP). The results revealed that the contribution of generated livestock technologies through annual investment Tk.1.65 million in livestock research, which was increased livestock GDP by Tk. 3,044.56 million annually which saved Tk. 2913.93 million of import expenditures of livestock products from outside countries. Therefore, to save significant amounts of foreign exchange through reducing imports and earn more foreign exchange through export; more investment on livestock research is needed. Hence, further national economic development, Bangladesh government must emphasize research investment for generating livestock technologies. Bangladesh J. of Livestock Res. 20(1-2): 77-87, Jan-Dec 2013